2018
DOI: 10.5194/esd-9-135-2018
|View full text |Cite
|
Sign up to set email alerts
|

Selecting a climate model subset to optimise key ensemble properties

Abstract: Abstract. End users studying impacts and risks caused by human-induced climate change are often presented with large multi-model ensembles of climate projections whose composition and size are arbitrarily determined. An efficient and versatile method that finds a subset which maintains certain key properties from the full ensemble is needed, but very little work has been done in this area. Therefore, users typically make their own somewhat subjective subset choices and commonly use the equally weighted model m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
136
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 38 publications
0
136
0
Order By: Relevance
“…This needs to be reconsidered given that multimodel ensembles contain near replicates of the same model that are not independent anymore Knutti et al, 2013;Masson & Knutti, 2011). Several methods have been proposed to take into account performance and/or interdependence when calculating multimodel averages (e.g., Abramowitz & Bishop, 2015;Abramowitz et al, 2008;Herger et al, 2018;Karpechko et al, 2013;Sanderson et al, 2015aSanderson et al, , 2015bTebaldi et al, 2006;Waugh & Eyring, 2008). Most of these approaches are rather complex, and so far no agreement was reached about which method should be used in general, how model dependence should be defined, and how it could best be accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…This needs to be reconsidered given that multimodel ensembles contain near replicates of the same model that are not independent anymore Knutti et al, 2013;Masson & Knutti, 2011). Several methods have been proposed to take into account performance and/or interdependence when calculating multimodel averages (e.g., Abramowitz & Bishop, 2015;Abramowitz et al, 2008;Herger et al, 2018;Karpechko et al, 2013;Sanderson et al, 2015aSanderson et al, , 2015bTebaldi et al, 2006;Waugh & Eyring, 2008). Most of these approaches are rather complex, and so far no agreement was reached about which method should be used in general, how model dependence should be defined, and how it could best be accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Since evaluating response bias to long-term changes in radiative forcing using multiple observational products is not common practice in the event attribution community, we suggest that the long-term response to forcing be evaluated and should be part of the optimization process if this characteristic of the raw model output is deemed unfit for purpose (in addition to distribution properties). The difficulty here however is that the nature of the long-term temperature response in-sample does not seem to persist out-of-sample (see, e.g., Figure 4 in Herger et al (2018)). Knutti and Hegerl (2008) showed that it is possible for two climate models to very closely track historical warming trends but behave completely different thereafter (their Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…The results of multivariate evaluation of the similarities and relationships within the multi-model ensemble could be a basis for selection of representative models to be used in impact studies. Previously proposed procedures, such as in Mendlik and Gobiet (2016) or Herger et al (2018), could be modified to use the FDA similarities introduced here. 30…”
Section: Discussionmentioning
confidence: 99%